Implementation of Islamic Education through Religious Character at SMK Darussalam Karangpucung Cilacap - Guntur Dwi Purwanto; Fauzi Fauzi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Islamic religious education is needed to shape the religious character of students into better people. This study aims to describe and explain the existence of Islamic education activities through religious characters. This research is included in a qualitative descriptive study because this study describes the process of forming the religious character of students through religious learning activities carried out at SMK Darussalam Karangpucung. The data analysis technique in this study includes several stages, namely a) data reduction, namely collecting and grouping data, b) presenting data, this activity describes and explains data, and c) concluding, in this activity, namely drawing conclusions after reducing and presenting data. The results of this study are finding several implementations of the formation of students 'religious character through several religious activities, including a) praying before and after learning, reading Asmaul Husna and Juz' Amma, b) Lecture 10 minutes, c) playing infaq, d) sunnah prayers, e) compulsory prayers (noon prayers), f) healthy Fridays, clean Fridays, Taqwa Fridays, and Literacy Fridays, and g) saying greetings when meeting residents of SMK Darussalam Karangpucung ( Teachers, friends, administration and so on).